COMPARATIVE STUDY OF THE USE OF WHATSAPP GROUP AND GOOGLE CLASSROOM LEARNING MEDIA TOWARDS LEARNING OUTCOMES FOR IPS CLASS IX SEMESTER 1 SMP NEGERI 1 GABUS - Eni Rosida (Literasi Nusantara, 2022)
This comparative study research aims to analyze the improvement of learning outcomes and analyze the effectiveness of the use of WhatsApp Group and Google Classroom Learning Media on learning outcomes during a pandemic emergency in class IX of SMP N 1 Gabus, Grobogan Regency. The quantitative approach includes: 1) analyzing the improvement of learning outcomes; 2) analyze the effectiveness of the media. The trial was carried out on 64 students, 32 students in class IX A used WhatsApp Group and class IX B had 32 students using Google Classroom. Data were collected by observation and documentation. The data on the effectiveness of the learning media were analyzed by means of gain, normality, and t-test at a significance level of 0.05. The results of the comparative study for class IX A. Based on the calculation of N-gain, the results of the pre-test and post-test results for class IX A were 0.67 in the moderate category. Regarding the results of calculations in class IX B, there is an increase in N-gain with a score of 0.70 in the high category with an average pre-test score of 84 and post-test scores of 91. The significance value is 0.000 < = 0.05, which means there is a significant difference between the average posttest learning outcomes between Class IX A (WhatsApp Group) and Class IX B (Google Classroom). This shows that the post-test average for Class IX B (Google Classroom) is higher than the post-test average for Class IX A (WhatsApp Group) and thus H1 is accepted.